The attitude of Sunni scholars towards the mystical interpretation of Ismailism - Marie, Farsat I. (Humanities Journal of University of Zakho, 2018)
Subinterpretation is an intellectual phenomenon characterized by Ismailia,The Ismailia went on to say that everything (= visible phenomenon) has a mystical interpretation that is only known to those who are established in science and are the imams,And these imams entrust this sub-science to the senior preachers in a certain extent, because the interpretation of the sublime God has singled him up,Just as the Prophet (peace and blessings of Allah be upon him) favored downloading, so did Ali ibn Abi Talib, who singled out the interpretation,This research is concerned with clarifying the Ismailia team and the fundamentals on which it was based, specifically the interpretation,And then the positions and responses of the scholars of the Sunnis and the community in all their different aspects of Ismailia mystical interpretation.